2021
DOI: 10.1161/circoutcomes.120.007546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Preeclampsia With Maternal Place of Birth and Duration of Residence Among Non-Hispanic Black Women in the United States

Abstract: Background: Preeclampsia is one of the leading causes of maternal mortality in the United States. It disproportionately affects non-Hispanic Black (NHB) women, but little is known about how preeclampsia and other cardiovascular disease risk factors vary among different subpopulations of NHB women in the United States. We investigated the prevalence of preeclampsia by nativity (US born versus foreign born) and duration of US residence among NHB women. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 40 publications
4
51
0
Order By: Relevance
“…The study also observed that US nativity worsened the risk of adverse outcomes while nulliparity was protective. Our findings and other recent publication from the BBC [ 28 , 29 ] corroborate the healthy migrant theory [ 30 ] which has been documented among South America and Asia born US migrants [ 31 ]. However, given this study does not disaggregate women by race and nativity, the degree to which this would apply to Black migrants specifically and warrants further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…The study also observed that US nativity worsened the risk of adverse outcomes while nulliparity was protective. Our findings and other recent publication from the BBC [ 28 , 29 ] corroborate the healthy migrant theory [ 30 ] which has been documented among South America and Asia born US migrants [ 31 ]. However, given this study does not disaggregate women by race and nativity, the degree to which this would apply to Black migrants specifically and warrants further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…47 This protective advantage of individuals born outside the US has been demonstrated among non-Hispanic Black women with shorter but not longer duration of US residence. 9 With longer duration of US residence, non-Hispanic Black women born outside the US adopt US behaviors such as smoking, which worsen their cardiovascular risk profile and health outcomes, thus losing the protective advantage of their nativity. 48 As has been described among non-Hispanic Black women, US-born Hispanic and non-Hispanic White women had higher prevalence of obesity, smoking, and complaints of severe stress compared with Hispanic and non-Hispanic White women born outside the US, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although some studies have found Hispanic ethnicity to be independently associated with increased risk of preeclampsia, 6 others have found Hispanic women to have a less or similar risk of preeclampsia compared with non-Hispanic White women despite poorer socioeconomic profiles. 7,8 Previous studies 9,10 demonstrated the association of maternal nativity and duration of US residence with preeclampsia among non-Hispanic Black women. Non-Hispanic Black women who are born outside the US tend to have a lower prevalence of preeclampsia and other cardiovascular risk factors than their US-born counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations